Effects of low-level laser therapy (LLLT 808 nm) on lower limb spastic muscle activity in chronic stroke patients. Issue 7 (September 2016) - Neves, Marcele; Reis, Mariana; Andrade, Eliana; Lima, Fernanda; Nicolau, Renata; Arisawa, Emília; Andrade, Adriano; Lima, Mário
Abstract A cerebrovascular accident (CVA) may affect basic motor functions, including spasticity that may be present in the upper extremity and/or the lower extremity, post-stroke. Spasticity causes pain, muscle force reduction, and decreases the time to onset of muscle fatigue. Several therapeutic resources have been employed to treat CVA to promote functional recovery. The clinical use of low-level laser therapy (LLLT) for rehabilitation of muscular disorders has provided better muscle responses. Thus, the aim of this study was to evaluate the effect of the application of LLLT in spastic muscles in patients with spasticity post-CVA. A double-blind clinical trial was conducted with 15 volunteer stroke patients who presented with post-stroke spasticity. Both males and females were treated; the average age was 51.5 ± 11.8 years old; the participants entered the study ranging from 11 to 48 months post-stroke onset. The patients participated in three consecutive phases (control, placebo, and real LLLT), in which all tests of isometric endurance of their hemiparetic lower limb were performed. LLLT (diode laser, 100 mW 808 nm, beam spot area 0.0314 cm2, 127.39 J/cm2 /point, 40 s) was applied before isometric endurance. After the real LLLT intervention, we observed significant reduction in the visual analogue scale for pain intensity (p  = 0.0038), increased time to onset of muscle fatigue (p  = 0.0063), and increased torque peak (p  = 0.0076), but no significant change in the root mean square (RMS) value (electric signal in the motor unit during contraction, as obtained with surface electromyography). Our results suggest that the application of LLLT may contribute to increased recruitment of muscle fibers and, hence, to increase the onset time of the spastic muscle fatigue, reducing pain intensity in stroke patients with spasticity, as has been observed in healthy subjects and athletes.